Nanophytosomes as a protection system to improve the gastrointestinal stability and bioavailability of phycocyanin - Sahin, Oya Irmak; Dundar, Ayse Neslihan; Ozdemir, Sebahat; Uzuner, Kubra; Parlak, Mahmud Ekrem; Dagdelen, Adnan Fatih; Saricaoglu, Furkan Turker (Elsevier, 2022)
Nano-phytosomes (NP), lipid-based nano-carriers, were used to encapsulate the phycocyanin. Phycocyanin (Phy) is known for its important biological properties with low bioavailability and low stability. The aim of the study was to prepare phosphatidylcholine (PC) based Phy loaded NP to overcome the bioavailability and storage stability issues. The characterization of NP such as entrapment efficiency (EE), particle size, poly-dispersity index (PDI), zeta-potential and microstructural properties was conducted and in vitro bioaccessibility and storage stability of bioactive properties were investigated. The highest EE was determined as 81.92% however with a loading capacity (LC) of 58.12%. Phy-NPs showed good characteristics, such as low PDI values (<0.5), low particle size (106.13-134.10 nm), and non-dense spherical shape of microstructure. All NP complexes showed significant bioaccessibility with total phenolic content (TPC) values greater than 50% in intestinal tract. Unfortunately, PC based NP did not show a clear-cut pattern of TPC and color protection of Phy via increased PC content.
Keywords: Phycocyanin; Phytosome; Phytochemical; Nanocarrier; Stability; In vitro bioaccessibility